Tata Laksana Refluks Gastroesofageal pada Anak: Tinjauan Pustaka - Diva Putra, Agus Indra Yudhistira; Ratih, Luh Putu Winansari; Limantara, Veronica Lily; Aurelya, Anira Rema; Arta, Komang Sutama; Tandiono, Erick Kusuma (Cermin Dunia Kedokteran, 2025)
Gastroesophageal reflux is common in adult population but mostly underdiagnosed in pediatric population. Diagnosis of gastroesophageal reflux in children is difficult and may masquerade as other gastrointestinal disease. This review discusses the management of gastroesophageal reflux in children especially in primary health care center to facilitate initial treatment and referral as needed.